Chopping spree - Davidson, Diane Mott. (New York : Bantam Books, 2002)
Asked to cater an event for the over-privileged "elite shoppers" of Westside Mall, Colorado chef Goldy B. Schulz finds herself embroiled in an investigation involving a psychopathic serial killer.
"A Bantam Book."--Title page verso.
Includes index.
Keywords: Bear, Goldy (Fictitious character) -- Fiction; Women in the food industry -- Fiction; Caterers and catering -- Fiction; Cooking -- Fiction; Colorado -- Fiction; Detective and mystery stories; Fiction; Humorous fiction